Amana yunmengensis (Liliaceae), a new species from the Yunmeng Lakes region, China - Wang, Meizhen; Wang, Ziyi; Zhang, Shenglu; Wu, Jing; Li, Pan (Phytotaxa, 2023)
Amana yunmengensis, a new species from Yunmeng Lakes region in China is described and illustrated in this study. It resembles A. edulis and A. baohuaensis but differs in several features. The principal components analysis of morphological data identified four distinct clusters: A. anhuiensis, A. edulis, A. hejiaqingii and A. yunmengensis. Cytological observation revealed that A. yunmengensis is diploid (2n = 2x = 24). Molecular phylogenetic analyses further support it as a new species.